Moisture chamber goggles for the treatment of postoperative dry eye in patients receiving SMILE and FS-LASIK surgery - Tianze Huang; Yuchen Wang; Zhou Zhu; Qingyang Wu; Di Chen; Ying Li (BMC Ophthalmology, 2023)
Abstract Background The incidence of refractive surgery-related dry eye disease (DED) is rising due to the increasing popularity of corneal refractive surgery. The moisture chamber goggles (MCGs) have been shown to tear evaporation by increasing local humidity and minimizing airflow. The current study aims to evaluate the efficacy of moisture chamber goggles for refractive surgery-related DED. Methods In this nonrandomized open-label controlled study, 78 participants (156 eyes) receiving refractive surgery were enrolled between July 2021 and April 2022, and sequentially allocated to MGC and control groups. 39 participants were allocated to the MGC groups, of which 53.8% received small-incision lenticule extraction (SMILE) and 46.2% received femtosecond laser-assisted in situ keratomileusis (FS-LASIK), and were instructed to wear MCGs for the duration of 1 month postoperatively, in addition to the standard postoperative treatment received by the control groups (56.4% SMILE, 43.6% FS-LASIK). Participants underwent full ophthalmic examinations, including visual acuity, manifest refraction, DED evaluations, and higher-order aberrations (HOAs), both preoperatively and at routine follow-ups 1 day, 1 week, and 1 month after surgery. DED parameters included non-invasive tear film break-up time (NIBUT), tear meniscus height (TMH), conjunctival congestion, lipid layer thickness (LLT), and ocular surface disease index (OSDI) questionnaires. Student’s t-test was used for comparisons between control and MCG groups, and between preoperative and postoperative parameters within groups. Results Postoperative NIBUT decreased in both SMILE and FS-LASIK control groups 1 day after the surgery (SMILE, P = 0.001; FS-LASIK, P = 0.008), but not in the corresponding MCG groups (SMILE, P = 0.097; FS-LASIK, P = 0.331). TMH in the MCG group was significantly higher at 1 week (P = 0.039) and 1 month (P = 0.015) in SMILE, and 1 day (P = 0.003) in FS-LASIK groups. In FS-LASIK participants, significantly lower HOAs and coma levels in the MCG group were observed 1 day (total HOAs, P = 0.023; coma, P = 0.004) and 1 week (total HOAs, P = 0.010, coma, P = 0.004) after surgery. No consistent statistically significant intergroup difference was observed between MCG and control groups in conjunctival congestion, LLT, and OSDI. Conclusions MCGs effectively slowed tear evaporation, increased tear film stability, and improved HOAs in patients receiving SMILE and FS-LASIK surgeries. MCG is an effective adjuvant therapy in the comprehensive management of refractive surgery-related DED.